2009
DOI: 10.1016/j.exer.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of the actomyosin system in regulating trabecular fluid outflow

Abstract: Abnormally high resistance to aqueous humor drainage via the trabecular meshwork and Schlemm's canal is highly correlated with the development of primary open-angle glaucoma. Contractility of the actomyosin system in the trabecular cells or inner wall endothelium of Schlemm's canal is an important factor in the regulation of outflow resistance. Cytoskeletal agents, affecting F-actin integrity or actomyosin contractility, or gene therapies, employing over-expression of caldesmon or Rho-A inhibition, can decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
106
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 36 publications
2
106
0
Order By: Relevance
“…Regulation of mechanical and contractile properties of the pressure-sensitive TM cells is recognized to play a significant role in modulation of aqueous humor outflow and ocular pressure homeostasis (22,29,41,58,60). Although there is a substantial amount of phenomenological data in the literature regarding the possible role of the ECM and cytoskeletal integrity in modulation of aqueous humor outflow, the mechanistic understanding for these interactions has lagged behind (24,41,49,51). Thus identifying the molecular basis by which the ECM, cytoskeletal integrity, cellular tension, and mechanostransduction modulate outflow facility through the TM is vitally important for understanding of homeostasis of intraocular pressure.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Regulation of mechanical and contractile properties of the pressure-sensitive TM cells is recognized to play a significant role in modulation of aqueous humor outflow and ocular pressure homeostasis (22,29,41,58,60). Although there is a substantial amount of phenomenological data in the literature regarding the possible role of the ECM and cytoskeletal integrity in modulation of aqueous humor outflow, the mechanistic understanding for these interactions has lagged behind (24,41,49,51). Thus identifying the molecular basis by which the ECM, cytoskeletal integrity, cellular tension, and mechanostransduction modulate outflow facility through the TM is vitally important for understanding of homeostasis of intraocular pressure.…”
mentioning
confidence: 99%
“…Supportive evidence for this link comes from perfusion studies that used cytoskeletal modulating agents, such as actin depolymerizing agents, inhibitors of myosin light-chain kinase, myosin II, protein kinase C, Rho GTPase, and Rho kinase and from both in vitro and in vivo model systems (11,19,41,51). These studies suggest that agents that increase actin depolymerization and decrease cell-ECM interactions and myosin II phosphorylation within cells of the trabecular pathway increase aqueous humor outflow presumably by causing cellular relaxation and by altering the geometry and stiffness of the outflow pathway tissues and fluid flow through the inner wall of SC (41,51).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Honjo (2001) concluded that Y-27632 had reduced the intraocular pressure significantly in rabbits. Cellular changes of trabecular meshwork and ciliary muscle relaxation were considered to be the underlying mechanism [4,5,6].…”
Section: Introductionmentioning
confidence: 99%